6(u+4)=-4(4u-4)+6u

Simple and best practice solution for 6(u+4)=-4(4u-4)+6u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(u+4)=-4(4u-4)+6u equation:



6(u+4)=-4(4u-4)+6u
We move all terms to the left:
6(u+4)-(-4(4u-4)+6u)=0
We multiply parentheses
6u-(-4(4u-4)+6u)+24=0
We calculate terms in parentheses: -(-4(4u-4)+6u), so:
-4(4u-4)+6u
We add all the numbers together, and all the variables
6u-4(4u-4)
We multiply parentheses
6u-16u+16
We add all the numbers together, and all the variables
-10u+16
Back to the equation:
-(-10u+16)
We get rid of parentheses
6u+10u-16+24=0
We add all the numbers together, and all the variables
16u+8=0
We move all terms containing u to the left, all other terms to the right
16u=-8
u=-8/16
u=-1/2

See similar equations:

| 3/2n=-1/9 | | 156-y=211 | | c+6=-1 | | -3(-7+4)-9u=2(u-9)-2 | | 7(x+6)=-4(3x-7)+x | | 7(u+2)=70 | | (x-4)/(x-3)=1 | | -18+3h=69 | | -5(-5u+7)-6u=7(u-7)-2 | | |8x+9|=33 | | -7(j+2)=-84 | | -4(x+4)=7x-27 | | −7.85=x/3.14 | | 5x2−6x−1=0 | | 5/9w+1/9w=5+(-2) | | 9+3(3y-3)=-2(5y-3)+y | | -5=-7x+4(x-5) | | 5u+1-4(-2u-2)=3(u-2) | | 25-4s=5 | | -46p-6.3p+3.9=9.18 | | -5x+10+9x=15 | | 6x+4+90+2x+10=180 | | 3y=-1.5 | | 12=6(q-96) | | 6x+1=x+7-x | | 2^n=9/32 | | n/45=-9 | | 3p+5=7p-7 | | -12b-1=-13b-20 | | -2x+16=16 | | 6b-8=82 | | 1/2(2.5+b2)(3)=30 |

Equations solver categories